2010
DOI: 10.1007/s11434-010-4010-x
|View full text |Cite
|
Sign up to set email alerts
|

Strontium and boron isotopic constraint on the marine origin of the Khammuane potash deposits in southeastern Laos

Abstract: Since 2006, we have conducted a geological exploration of the Khammuane area in southeastern Laos. Several thick sequences of potash deposits containing sylvite and carnallite were discovered from drilling Paleocene strata of the Thangon Formation (E 1 tg).To constrain the origin of the brine that formed thick sequences of salt mineral deposits, we measured the strontium and boron isotope composition of some salt minerals in the potash deposit. Boron isotope composition of halite-and potash-associated minerals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Sulfur isotopes from anhydrites (El Tabakh et al, 1999) falling in the range of marine evaporites implied their seawater origin. Evidence from boron isotope composition in fluid inclusions of halite showed that it differed significantly from that of continental evaporites and is very close to that of salts precipitated from evapo-concentrated seawater (Tan et al, 2010). Based on the lack of evidence suggesting transgression, some authors insisted that the Maha Sarakham Formation is not of marine origin (Utha-Aroon, 1993;Meesook, 2000;Racey and Goodall, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur isotopes from anhydrites (El Tabakh et al, 1999) falling in the range of marine evaporites implied their seawater origin. Evidence from boron isotope composition in fluid inclusions of halite showed that it differed significantly from that of continental evaporites and is very close to that of salts precipitated from evapo-concentrated seawater (Tan et al, 2010). Based on the lack of evidence suggesting transgression, some authors insisted that the Maha Sarakham Formation is not of marine origin (Utha-Aroon, 1993;Meesook, 2000;Racey and Goodall, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Through studies on the borates, we attempted to use the boron isotopic composition of borates to reveal the origin of potash-bearing evaporites on the Khorat Plateau. Because of the significantly different range of marine and nonmarine borates (averaging +25 ± 4‰ and À7 ± 10‰, respectively), the boron isotopic composition of borates has widely been used to distinguish marine and nonmarine sedimentary environments or the origin of fluids from which they precipitate in many evaporite deposits (Swihart et al, 1986;Oi et al, 1989;Vengosh et al, 1992;Grice et al, 2005;Tan et al, 2010). In this paper, we also attempted to characterize the changes of boron isotopic composition and discuss its influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…Br/Cl molar ratios have also frequently been used by many studies to determine whether the origin of water is marine or non-marine (Swihart and Moore, 1986;Utha-Aroon, 1993;Vengosh et al, 1995;El Tabakh et al, 1999;Taberner et al, 2000;Rahimpour-Bonab and Kalantarzadeh, 2005;Kendrick et al, 2006;Tan et al, 2010). The typical Br/Cl × 10 −3 molar ratio is~0.11 mmol/mol in the halite stage during seawater evaporation, 0.31 mmol/mol in the sylvite stage, 0.45 mmol/mol in the carnallite stage and 0.68 mmol/mol in the final stage ( Fig.…”
Section: Variation Of Br I Br/cl and I/cl In Halitementioning
confidence: 99%
“…Warren, 1989Warren, , 2006Warren, , 2010Utha-Aroon, 1993;Qian et al, 1994;El Tabakh et al, 1998Rahimpour-Bonab and Kalantarzadeh, 2005;Cendón et al, 2008;Talbot et al, 2009aTalbot et al, , 2009bTan et al, 2010;Tong et al, 2013;Zhang et al, 2013). Potash deposits typically originate from brines of marine or/and land origin(s), along with varying inputs from deeplycirculating meteoric, basinal and hydrothermal fluids (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation